A Narrative Review of Regional Hyperthermia: Updates From 2010 to 2019. (October 2020) - Fiorentini, Giammaria; Sarti, Donatella; Gadaleta, Cosmo Damiano; Ballerini, Marco; Fiorentini, Caterina; Garfagno, Tommaso; Ranieri, Girolamo; Guadagni, Stefano
The role of hyperthermia (HT) in cancer therapy and palliative care has been discussed for years in the literature. There are plenty of articles that show good feasibility of HT and its efficacy in terms of tumor response and survival improvements. Nevertheless, HT has never gained enough interest among oncologists to become a standard therapy in clinical practice. The main advantage of HT is the enhancement of chemotherapy (CHT), radiotherapy (RT), chemoradiotherapy (CRT), and immunotherapy benefits. This effect has been confirmed in several types of tumors: esophageal, gastrointestinal, pancreas, breast, cervix, head and neck, and bladder cancers, and soft tissue sarcoma. HT effects include oxygenation and perfusion changes, DNA repair inhibition and immune system activation as a consequence of new antigen exposure. The literature shows a wide variety of randomized, nonrandomized, and observational studies and both prospective and retrospective data to confirm the advantage of HT association to CHT and RT. There are still many ongoing trials on this subject. This article summarizes the available literature on HT in order to update the current knowledge on HT use in association with RT and/or CHT from 2010 up to 2019.